2023
DOI: 10.1088/0256-307x/40/8/086102
|View full text |Cite
|
Sign up to set email alerts
|

Route to Stabilize Cubic Gauche Polynitrogen to Ambient Conditions via Surface Saturation by Hydrogen

Abstract: Cubic gauche polynitrogen (cg-N) is an attractive high-energy density material. However, high-pressure synthesized cg-N will decompose at low-pressure and cannot exist at ambient conditions. Here, the stabilities of cg-N surfaces with and without saturations at different pressures and temperatures are systematically investigated based on first-principles calculations and molecular dynamics simulations. Pristine surfaces at 0 GPa are very brittle and will decompose at 300 K, especially (1 1 0) surface will coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…They found that the hydrogen saturation of its surface can stabilize the cg-N to 750 K at 0 GPa. [1] This successful interception of cg-N by hydrogen saturation indicates that making a constraint on the surface of polymeric nitrogen can significantly enhance its stability even realize the interception at ambient conditions. This urges us to search for other effective constraint methods to improve the stability of polymeric nitrogen.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…They found that the hydrogen saturation of its surface can stabilize the cg-N to 750 K at 0 GPa. [1] This successful interception of cg-N by hydrogen saturation indicates that making a constraint on the surface of polymeric nitrogen can significantly enhance its stability even realize the interception at ambient conditions. This urges us to search for other effective constraint methods to improve the stability of polymeric nitrogen.…”
mentioning
confidence: 91%
“…The exploitation of polymeric nitrogen is always an active research topic for their potential applications in energy storage, propellants, and explosives. [1][2][3][4][5] A great deal of polymeric nitrogen structures have been proposed theoretically, such as zero-dimensional (0-D) caged structure (N10), [6] one-dimensional (1-D) chain-like structure (CH), [7] two-dimensional (2-D) layered structures [black phosphorus nitrogen (BP-N), layered polymeric nitrogen (LP-N), hexagonal layered polymeric nitrogen (HLP-N), arsenic (A7), layered-boat (LB), 𝑃 21], [6,[8][9][10][11][12] and threedimensional (3-D) networked structures [cubic gauche nitrogen (cg-N), chaired web, Pnnm, Cccm]. [8,[13][14][15] Up to date, only a few of structures have been successfully synthesized at extreme conditions, including the cg-N (110 GPa, 2000 K), LP-N (150 GPa, 3000 K), HLP-N (244 GPa, 3300 K), and BP-N (146 GPa, 2200 K), which can be quenched to 42 GPa, 52 GPa, 66 GPa, and 48 GPa, respectively.…”
mentioning
confidence: 99%
“…More recently, it has been observed that cg-N can exhibit stability in an acidic condition or when the surface is saturated with less electronegative adsorbates. [34] Numerous planar or quasiplanar cyclo-N 6 anions have been predicted in Li, Mg, Ca, and Ba nitrides under high pressure. [7,[35][36][37] However, they have not paid close attention to the microstructural characteristics of these cyclo-N 6 anions.…”
Section: Introductionmentioning
confidence: 99%